Nutritional value of foods: a situation of study to contextualization and interdisciplinarity in science teaching - Marli Spat Taha; Alexandre de Souza Javorsky; Cátia Silene Carrazoni Lopes Viçosa; Emerson de Lima Soares; Maristela Cortez Sawitzki (Universidad Distrital Francisco José de Caldas, 2017)
This paper contains a proposal of teaching strategy based on a situation of study, which uses three pedagogical moments: initial problematization, knowledge organization, and knowledge systematization, as a planning way of the proposed activity. In addition, it proposes to contextualize the situation of study in an interdisciplinary strategy from the theme "Healthy Eating", mentioning some concepts of Natural Sciences that can be approached in the case of this situation of study. This experience occurs from a lunch in a school, enabling a knowledge problematization and providing strategies to the construction of situation of study.